Positive psychology pioneers: Professor Martin Seligman's power and potential to influence mental health nursing. (2nd February 2022) - Macfarlane, Jan
Abstract : This article introduces a series that will celebrate the work of positive psychologists and discuss how their work has the power and potential to influence mental health nursing practice. The series will provide a historical perspective of early psychologists, their contributions and the continued importance of recognising current positive psychologists, as they also revive and regenerate understanding of the study of the individual. The first paper in the series focuses on the work of Professor Martin Seligman and his interest in optimism and positivity. He is regarded by many as 'the father of positive psychology'.